Development Of Maintenance Policy Selection (MPS) Model To Select The Optimal Maintenance Policy For A System In Palm Oil Mill - Ding , Siew Hong (2010)
The maintenance is change due to the development of technology. Under the changes, different maintenance policies have been developed, from corrective maintenance until predictive maintenance. Penyelenggaraan telah berubah dengan perkembangan teknologi. Di bawah perubahan ini , pelbagai jenis dasar penyelenggaraan telah dibangunkan